Mechanism and experimental evidence of rapid morphological variant of copper oxide nanostructures by microwave heating - Karakade Kaewyai (2018)
© 2018 Elsevier B.V. In this work, the formation mechanisms under rapid microwave radiation of copper oxide nanofibers and copper oxide nanoparticles were proposed. The copper oxide nanofibers were synthesized by using only pure copper powders. Whereas, ethanol addition in pure copper powders significantly influenced nucleation and morphological formation of the copper oxide nanoparticles. Both nanofibers and nanoparticles were determined by X-ray diffractometer (XRD) showing a mixture of Cu2O and CuO phases. The mixed structures were clearly confirmed by transmission electron microscope (TEM). The copper oxide nanofiber diameters were in the range of 500–5,500 nm with an average length of about 2.5 cm and a circular cylindrical shape and smooth surface. The nanoparticles showed a spherical shape with homogeneous size in the diameter range of 80–120 nm. This report further investigated a formation mechanism using experimental results. The study showed that the formation could be attributed to surface reactions of ethanol in polar characteristic way that accumulated thermal into Cu powders.